The Dynamics of Share-Price Formation - Tinbergen, J. (The Review of Economics and Statistics, 1939)
In a recent investigation which the author has made for the League of Nations Secretariat, it was found that share prices seem to have exerted a considerable influence on the course of the American cycle beginning in 1924 and having its boom year in 1929. The chief reason for this influence may be summarized briefly as follows: (a) Share prices have an influence on the ease with which capital issues may be floated and therefore on investment activity in general; (b) the rate of increase in share prices seems to have an influence on consumption, especially by those making capital gains. These influences have been investigated in the forthcoming League of Nations publication and will not be treated in detail now, but it may be seen from this brief indication that the formation of share prices seems to be important in the explanation of some business-cycle phenomena. This is the justification for the present paper, which deals only with that price formation.